Impact of Tussigenic Stimuli on Perceived Upper Airway Sensation and Motor Cough Response Following Total Laryngectomy - Fullerton, Amy; Mou, Yuhan; Silver, Natalie; Chheda, Neil; Bolser, Donald C.; Wheeler-Hegland, Karen (Frontiers in Physiology, 2020)
Background Total laryngectomy is standard intervention for carcinoma of the head and neck or in cases of non-functional larynx as a result of disease or radiation exposure. Laryngeal extirpation serves as a unique human model of both recurrent and superior laryngeal nerve section and offers insight into motor and sensory aspects of cough: both volitional and in response to tussigenic stimuli. While motor changes in cough function are expected among those status post total laryngectomy (TL) due to postoperative reconstruction of the upper airway, motor cough parameters have not been well described and sensory aspects of cough are unknown in this population which provides the insight of a vagal denervation model in humans. Method(s) Data were collected from three groups totaling 80 adults (39 male), including 25 healthy, young adults (HYA), 27 healthy older adults (HOA) and 28 adults post TL. Cough was elicited both upon command and in response to nebulized capsaicin. Outcome measures included urge-to-cough and cough airflows. Results Kruskal Wallis test showed that two of the three groups differed significantly by urge to cough x2(2, N=244) =8.974, p=0.011. Post hoc analysis showed that post TL subjects had reduced perceived urge to cough at all concentrations of capsaicin (p<0.05). Cough airflows were significantly reduced for post TL subjects compared to healthy controls in all metrics except post-peak phase integral (PPPI) for which HOA and TL’s were comparable under both volitional and capsaicin-induced conditions. Conclusions These findings support the hypothesis that both cough airflow and sensations are significantly reduced in post TL subjects when compared with HOA. Interestingly, HOA and post TL subjects have comparably reduced UTC and cough airflows when compared to HYA. The only metric of cough airflow for which these groups differ is the post-peak phase integral (PPPI) which may be a compensatory adaptation for reduced cough airflows and/or sensation.